(untitled) (Asian Journal of Medical and Biological Research, 2017)
In order to understand the present status of hatcheries, questionnaire interview and participatory rural appraisal tools were used in North-west Fisheries Extension Project (NFEP), Parbatipur during the period from July to December 2015. There are two hatcheries in NFEP, Parbatipur- a carp hatchery and a prawn hatchery. The production of spawn was around 611 kg in the year 2015. According to the target hatchery manager collected brood fish from rivers and other sources which he maintained in their brood stock ponds with proper management. The hatchery manager maintained proper age and weight of broods for spawning and followed the guideline of hatchery operation so that the quality of spawn and fry were good. It was found that the hatcheries produced fish seed of a variety of species such as Indian major carps, carpio, sarpunti, silver carp, grass carp, magur, shing as well as freshwater prawn. The hatchery production activities took place starting from February and continued up to September. The quantity of fish seed produce varied from 25 to 75 kg per hatching cycle depending on size and facilities of hatcheries. The price of fry in NFEP was being fixed by the hatchery manager. However, the price variation was seen due to seasonal variation, species and demand. The average price of fish seed was highest in monsoon and lowest in winter. A number of middlemen were involved in the fry marketing channel of NFEP at Parbatipur. They were responsible for increasing the price of fry at each stage of marketing channel. Asian J. Med. Biol. Res. September 2017, 3(3): 368-378